Analysis of Provision of KIE on Food and Beverage Sanitation Hygiene on Knowledge and Attitudes of the Unemployed and Underemployed in Kediri Regency - Panca Radono; Nurwijayanti; Ema Mayasari; Laily Nurhanifah (Journal of Global Research in Public Health, 2022)
Food and drink can be contaminated which has an impact on the emergence of a disease. Contamination can cause food and drink to become a medium for a disease. Food-borne disease is a disease caused by contaminated food and drink. The purpose of this study was to determine the effect of giving IEC on food and beverage hygiene and sanitation on the knowledge and attitudes of the unemployed and underemployed in Batuaji Village, Kediri Regency, as many as 30 respondents. The results of this research activity indicate that the knowledge of the respondents is good. The results of the Wilcoxon test because the distribution of the data is not normal shows that there is no significant effect on the knowledge and attitudes of the respondents. But it has an average rating increase of 0.2 points. From the pre-test average of 9.5 to 9.7 in the post-test. So it can be concluded that this research has no effect on changes in the knowledge and attitudes of respondents.